Treatment satisfaction and quality of life of adolescents with T1DM using continuous subcutaneous insulin infusion - Lima, Lígia (2022)
Introduction: Continuous subcutaneous insulin infusion (CSII) has been prioritised in the metabolic control of type 1 Diabetes Mellitus (T1DM) in children and adolescents. Objective: To assess the quality of life and treatment satisfaction in adolescents with T1DM using CSII and analyse the role of quality of life in predicting treatment satisfaction among these adolescents. Methods: The sample comprised 77 adolescents aged 10 to 18, followed-up in two central hospitals in the Northern region of Portugal. The Quality-of-Life questionnaire for treatment with Insulin Infusion Pump – adolescents’ version - and the adapted version for adolescents of treatment satisfaction with Insulin Pump questionnaire were used. Results: Most adolescents reported a good quality of life, with lower values in the dimensions related to the Impact of Diabetes, Feelings and Mood and Leisure. They were satisfied with the CSII system, recognizing it as convenient, easy to use and guarantying autonomy. A prediction model was tested through multiple linear regression, with the Impact of diabetes, Leisure Time and Feelings and mood explaining 32.7% of the variance of treatment satisfaction. Conclusion: CSII is a therapeutic option that adolescents with T1DM perceive to promote their quality of life and consider satisfactory, in line with the previous evidence. However, interventions aimed to support these adolescents in managing their disease and treatment should focus on aspects such as self-image and emotional well-being.